Particle physics with gravitational wave detector technology. (19th September 2018) - Englert, Christoph; Hild, Stefan; Spannowsky, Michael
Abstract: Gravitational wave detector technology provides high-precision measurement apparatuses that, if combined with a modulated particle source, have the potential to measure and constrain particle interactions in a novel way, by measuring the pressure caused by scattering particle beams off the mirror material. Such a measurement does not rely on tagging a final state. This strategy has the potential to allow us to explore novel ways to constrain the presence of new interactions beyond the Standard Model of Particle Physics and provide additional constraints to poorly understood cross-sections in the non-perturbative regime of QCD and nuclear physics, which are limiting factors of dark matter and neutrino physics searches. Beyond high-energy physics, if technically feasible, the proposed method to measure nucleon-nucleon interactions can lead to practical applications in material and medical sciences.